2020
DOI: 10.1159/000508830
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Controlled Trial Evaluating Active versus Passive Waiting for Speech-Language Pathology

Abstract: <b><i>Introduction:</i></b> High demand for speech-language pathology means children sometimes wait over 12 months for services, missing out on timely support. Waiting can be a time of stress, concern, and powerlessness for caregivers. Provision of information via a website may support families and encourage active waiting. <b><i>Objective:</i></b> The aim of this study was to compare children’s speech, intelligibility, language, and literacy outcomes, and caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Even if therapy cannot be offered for a long time, processes are 'in motion' once an assessment is done" (160). In a recent community-based randomised controlled trial (RCT), provision of an assessment following referral to families on a speech and language therapy waiting list led to similar improvements in child outcomes and caregiver satisfaction to those who received both an assessment and access to an evidence-based speech and language website while waiting (McGill, McLeod, Ivory et al, 2021). However, Ruggero et al (2012) found that parents were dissatisfied with long waits between assessment and commencing therapy.…”
Section: Slt Service Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…Even if therapy cannot be offered for a long time, processes are 'in motion' once an assessment is done" (160). In a recent community-based randomised controlled trial (RCT), provision of an assessment following referral to families on a speech and language therapy waiting list led to similar improvements in child outcomes and caregiver satisfaction to those who received both an assessment and access to an evidence-based speech and language website while waiting (McGill, McLeod, Ivory et al, 2021). However, Ruggero et al (2012) found that parents were dissatisfied with long waits between assessment and commencing therapy.…”
Section: Slt Service Deliverymentioning
confidence: 99%
“…The results indicated that provision of advice sessions or a website to caregivers were not as effective as face-to-face therapy for improving children's speech production or caregivers' satisfaction, but there was little difference in outcomes across groups regarding children's intelligibility, language, and early literacy, and caregivers' feelings of empowerment (McLeod et al, 2020). A concurrent RCT by McGill, McLeod, Ivory et al (2021) compared two waiting list conditions: (1) provision of the same purpose-built website to caregivers; and (2) a control group involving provision of assessments only. The findings indicated that provision of a website was no more effective at improving children's and caregivers' outcomes than receiving an assessment only while waiting, suggesting families may require more than a generic website alone while waiting (McGill, McLeod, Ivory et al, 2021).…”
Section: Slt Service Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the lack of licensing portability across states, despite national accreditation standards and certification requirements, has impeded widespread adoption of telepractice services ( Jakubowitz, 2011 ). It is well-known that delayed or lack of services negatively impacts young and school-age children's development and education ( McGill et al, 2020 ). Although telepractice has been proposed as a potential means of reaching unserved or underserved populations ( Doarn et al, 2010 ), the approach remains underutilized ( Lowman & Kleinert, 2017 ).…”
mentioning
confidence: 99%